MINDFULNESS BREATHING, VISUAL, RELAXATION MODEL DEVELOPING DZIKIR TO IMPROVE TRANSCENDENT CHARACTER OF MADRASAH ALIYAH STUDENTS - Muhammad Muhib Alwi; Nur Hidayah; Nur Eva; Ika Andrini Farida (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
Madrasah Aliyah, an educational institution that combines conventional subjects with religious subjects, focuses on character development and academic skills. However, the evaluation of guidance counseling teachers on the transcendent character of Madrasah Aliyah students has not been optimally improved. Therefore, it is necessary to develop a psychological approach model to improve it. The purpose of this study is to develop a mindfulness breathing visual relaxation (BVR) model containing the recitation of Asmaul Husana to improve the transcendent character of Madrasah Aliyah students. The research method used is research and development (R&D) with 10 steps. This model was developed from a mindfulness strategy. Students' transcendent character was measured by the Self-Transcendence Scale (STS). Data analysis used an independent sample t-test on the pre-test and post-test scores of the experimental and control groups. The results showed that the mindfulness breathing visual relaxation model containing the recitation of Asmaul Husana was effective in improving the transcendent character of Madrasah Aliyah students with a significance value (2-tailed) of 0.000. The novelty of this research is that the mindfulness model, previously implemented using breathing, visualization, and relaxation (BVR) techniques, is complemented by the recitation of Asmaul Husana (The Beautiful Names of Allah) at each stage, including the phrases